An Integrated 28 GHz Front-End Module for 5G Applications in 45 nm PD-SOI - Ciocoveanu, Radu; Lammert, Vincent; Weigel, Robert; Issakov, Vadim (2019 IEEE MTT-S International Microwave Conference on Hardware and Systems for 5G and Beyond, IMC-5G 2019, 2019)
This paper presents an integrated 28 GHz front-end module (FEM) for 5th Generation (5G) applications and fabricated in a 45 nm partially depleted silicon on insulator (PD-SOI) technology. In transmit (Tx) mode at 28 GHz, the measured saturated output power (Psat), maximum power-added efficiency (PAEmax), output-referred 1-dB compression point (OP1dB) are 17.2 dBm, 26 % and 16.7 dBm, respectively, with 86.4 mW dc power consumption from a 1.8 V supply. In receive (Rx) mode at 28 GHz, the measured gain, noise figure (NF), input-referred 1-dB compression point (IP1dB) are 9dB, 3.6dB and -10dBm, respectively, with 14.8mW dc power consumption from a 1 V supply. The chip core size is 0.62mm x 0.75mm.
CRIS-Team Scopus Importer:2021-04-20